2020
DOI: 10.1186/s12877-020-1494-3
|View full text |Cite
|
Sign up to set email alerts
|

Supporting at-risk older adults transitioning from hospital to home: who benefits from an evidence-based patient-centered discharge planning intervention? Post-hoc analysis from a randomized trial

Abstract: Background: Subgroups of older patients experience difficulty performing activities of daily living (ADL) following hospital discharge, as well as unplanned hospital readmissions and emergency department (ED) presentations. We examine whether these subgroups of "at-risk" older patients benefit more than their counterparts from an evidence-based discharge planning intervention, on the following outcomes: (1) independence in ADL, (2) participation in life roles, (3) unplanned re-hospitalizations, and (4) ED pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 64 publications
0
18
0
2
Order By: Relevance
“…♀ 76% Control 82.9 (± 6.33, range n.r.) ♀ 80% Intervention Predischarge home visit Control Usual care ADL/IADL, Falls, re-hospitalization, institutionalization IADL [ 56 ], SMAF subscales [ 54 ] ADL subscales [ 57 ] number of recurring falls, mean number of fall recurrence in former fallers, number of re-hospitalizations, number of institutionalizations 12 Provencher et al, 2020 [ 27 ] a RCT, Post-hoc analysis Australia Acute care, unspecified n = 400 Intervention 80.2 (±6.4, range n.r.) ♀ 59.6% Control 80.7 (± 5.7, range n.r.)…”
Section: Resultsmentioning
confidence: 99%
“…♀ 76% Control 82.9 (± 6.33, range n.r.) ♀ 80% Intervention Predischarge home visit Control Usual care ADL/IADL, Falls, re-hospitalization, institutionalization IADL [ 56 ], SMAF subscales [ 54 ] ADL subscales [ 57 ] number of recurring falls, mean number of fall recurrence in former fallers, number of re-hospitalizations, number of institutionalizations 12 Provencher et al, 2020 [ 27 ] a RCT, Post-hoc analysis Australia Acute care, unspecified n = 400 Intervention 80.2 (±6.4, range n.r.) ♀ 59.6% Control 80.7 (± 5.7, range n.r.)…”
Section: Resultsmentioning
confidence: 99%
“…Australian study involving at risk older adults showed than an intervention to optimise discharge preparation and post discharge support in the community across ve sites signi cantly reduced unplanned admissions (22).…”
Section: Discussionmentioning
confidence: 99%
“…A partir de informações da literatura, observou-se que as ações desempenhadas pelos projetos estão de acordo com as recomendações atuais a respeito do cuidado ao paciente e atenção à família, além do papel da equipe assistencial neste processo. Dentre estas ações, podemos elencar o cuidado centrado no paciente considerando a individualidade, atenção às necessidades funcionais como parte da recuperação da sua doença, promoção do autocuidado e inclusão da família como parte fundamental nos processos assistenciais que envolvem o cuidado (PROVENCHER et al, 2020;DAHLKE et al, 2019;PETRY et al, 2019;CHAN;SAMSUDIN;LIM, 2019).…”
Section: Discussionunclassified